Attendance at Counseling Sessions Predicts Good Treatment Response in Methadone Maintenance Therapy - Othman, Zahiruddin; Gani, Firdaus Abdul (Japan International Cultural Exchange Foundation, 2017)
Objective: This study aimed to identify the predictors of good response in Methadone Maintenance Therapy (MMT) defined as retention and negative urine for opiate for 6 month after the enrollment. Methods: Across-sectional study from October 2007 to March 2008 was conducted on injecting drug users (IDUs) in the MMT programme at the Psychiatric Clinic, Hospital Raja Perempuan Zainab II (HRPZ II). Results: A total of 150 patients were studied. Good treatment response in MMT was seen in 55% of these patients. The only predictor of good treatment response in multivariate analyses was number of counseling sessions. For every increase in counseling sessions, a person has 1.2 times the chance of having a good outcome (Cl 1.049-1.349, p-value 0.007). Educational level, occupation, marital status, age and maintenance dose were not significantly associated with response in MMT Conclusion: Frequent attendance at counseling sessions was found to have a positive influence in the good treatment response in methadone therapy. Hence, it is an important component in the treatment of patients in MMT programme.